Interpersonal Communication Strategies in Single Mother Parenting to Strengthen Emotional Closeness with Children - Fara Nur Azizah; Herlina Suksmawati (Interaction Communication Studies Journal, 2026)
Families with single mothers face more complex challenges in carrying out parenting functions, particularly in building emotional closeness with their children without the presence of a father figure. Therefore, interpersonal communication is a crucial aspect in creating a harmonious relationship between mother and child. This study aims to analyze the interpersonal communication strategies of single mothers in building emotional closeness with their children in Sidoarjo Regency. The study used a qualitative descriptive approach with in-depth interviews with four single-mother families with children aged 13–18. Data analysis utilized the Miles and Huberman model, which included data reduction, data presentation, and conclusion drawing. The analysis was based on Devito's interpersonal communication theory, which encompasses five indicators: openness, empathy, support, positivity, and equality. The results showed that all informants implemented the five indicators of interpersonal communication at varying levels depending on the characteristics of the mother, the child, their family background, and their work demands. Openness fosters trust, empathy strengthens understanding of the child's emotional state, support is manifested through attention and motivation, positivity is reflected in appreciation, and equality provides space for children to express their opinions and participate in decision-making. This study concludes that the quality of interpersonal communication is a major factor in building a sense of security, comfort, mutual trust, and emotional closeness between single mothers and their children.